PARTAI POLITIK DAN LEMBAGA SWADAYA MASYARAKAT EKSISTENSI DAN PENGARUHNYA DALAM PEMBUATAN HUKUM - Sri Istiawati (Universitas Medan Area, 2013)
The concept of law as the rule of law does not appear suddenly but rather the result of the development of the reciprocal relationship between law and society itself. The law is not pure and clean from the various influences and interests that exist in the community either that of the political, social, cultural, economic, information and technology. Political influence is a very important factor, because the political intervention of the law is very dominant. This happens because of the political problems can not be divorced from the separate legal policy (Legal Police).